Examining the Academic Achievement–Delinquency Relationship Among Southeast Asian Americans. (May 2018) - Bui, Laura
The extent to which poor academic achievement is strongly related to delinquency among Southeast Asian Americans (SEAA) remains unclear; reasons are methodological limitations and aggregated findings for Asian Americans, which mask evidence that SEAA have a higher prevalence of criminality and poor academic performance than other Asian American groups. The present study examines the academic achievement—delinquency relationship in a diverse group of 1, 214 SEAA using data from the Children of Immigrants Longitudinal Study (CILS). Propensity score matching (PSM) was used to make causal inferences and assess whether poor academic achieving SEAA, after being matched with higher academic achieving SEAA, displayed a higher prevalence of delinquency. Findings showed that, even after matching, poor academic achieving SEAA were still more likely to exhibit delinquent behavior than those who performed academically better. Interventions targeting SEAA communities will need to focus more on improving academic achievement to directly prevent and decrease delinquent behavior.